BASLAWÍSH KLASS OQÍWSHÍLARÍNDA BAYLANÍSLÍ SÓYLEWDI QÁLIPLESTIRIWDIŃ TEORIYALÍQ HÁM METODIKALÍQ ÁHMIYETI - Reyembaeva, A.P. (SCIENCE and SOCIETY, 2024)
The article presents a number of concepts on the importance and tasks of the development of students' speech in primary education in the effective functioning of the continuous education system.